Study of the catch of white shrimp (Penaeus merguiensis) using Wangkong fishing gear in Demak Waters - Nurlaela, Yulfa Rahmanissa; Ayuningrum, Diah; Prakoso, Kukuh (Universitas Malikussaleh, 2025)
White shrimp (P. merguiensis) is the dominant catch caught in Demak waters and has high economic value. The fishing gear used by fishermen is wangkong fishing gear. This research aims to determine the composition and size structure of the catch, as well as the relationship between length and weight and sex ratio. The research was carried out in April and May 2024. The research method used was a survey method. The shrimp sampling method used is the census method. The target catch of fishermen from Menco Village, namely Penaeus merguiensis, was 87.10% and fishermen from Babalan Village, namely Penaeus merguiensis, amounted to 66.63%. The non-target catches were Mugil spp, Plotosuscanius, Rastrelliger spp, Scylla serrata, Oratosquilla oratoria, and Anguilla bicolor. The length class mode for white shrimp in Menco Village is 74.4 – 79.2 mm and Babalan Village is 96.6 – 106.5 mm. The relationship between length and weight of male white shrimp from Menco Village was obtained as W= 0.000353293L2.724 and female white shrimp from Menco Village was obtained as W= 0.000244543L2.837. The relationship between length and weight of male white shrimp from Babalan Village was obtained as W= 0.001095644L2.402 and female white shrimp from Babalan Village was obtained as W= 0.000167463L2.960. The sex ratio for white shrimp showed that the ratio between males and females in Menco Village was 1:1.10 and Babalan Village was 1:1.36. The growth pattern of P. merguiensis is negative allometric and more female shrimp are caught than male shrimp. Keywords: Catch; Demak Waters; Wangkong; WhiteShrimp (P. merguiensis)